(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: This article covers some theoretical and practical issues in the organization of independent work of students. This article examines the pedagogical conditions necessary for organizing independent work among students, focusing on theoretical and practical aspects. Independent work is highlighted as a vital component of the educational process, fostering autonomy, responsibility, and creativity in students. The study analyzes the challenges faced by educators in effectively implementing independent work and proposes innovative methods, including the integration of technology and interactive techniques. The findings emphasize the importance of structured guidance and resource accessibility to ensure the success of independent learning. This research contributes to the understanding of how to optimize independent work practices to enhance cognitive and practical skills in students.